Efecto de tres niveles de fertilización NPK en el rendimiento y calidad de Allium cepa L. VAR. SIVAN F1-H-202 EN SANTO DOMINGO, LAREDO-TRUJILLO - Ore Ore, Rafael Felipe (2015)
This research was conducted during the months of January to September 2015 in the farm Don José, located in Santo Domingo, Laredo district, Trujillo province, La Libertad region; Located 336 meters above sea level, with a temperate, dry and pleasant climate, with temperatures ranging between 16 ° C and 26 ° C with sunny days and cold nights by lowering temperature; rainfall is low throughout the year, except for the months when the entire northern coast of Peru rainfall presented by “El Niño” or when rains are excessive in winter time in the mountains, gets low to moderate precipitation intensity; in loamy sand soil texture, moderately saline and low in organic matter. The study aimed to evaluate the effect of three levels of NPK fertilization; and to determine the best dose of NPK fertilizer to obtain the highest performance and quality of Allium cepa L. Var. Sivan F1-H-202 in Santo Domingo, Laredo - Trujillo. The design of a randomized complete block, with four treatments and four repetitions. The treatments used were: 60- 60- 60 NPK (T0), this being the witness, 100- 80- 140 NPK (T1), 160- 100- 200 NPK (T2), and 220- 120- 260 NPK (T3). Statistical evaluation was based on the analysis of variance and Duncan test at the 0.05% level. The results indicate that the morphological and performance variables were statistically significant; in which treatment (T3) was the best of all treatments, achieving a yield of 55 275 kg.ha-1 and the highest quality of Allium cepa L. Var. Sivan F1-H-202 in Santo Domingo, Laredo - Trujillo.